(untitled) (Dhaka University Journal of Science, 2022)
Fourteen tropical fruit items were collected from different industrial sites of the Dhaka and Chattogram region, Bangladesh to determine toxic heavy metal contents. This study aimed at the assessment of the distribution of heavy metals (As, Pb and Cr) as well as comparison of their level among different locations. The fruit items were analyzed for the quantiﬁcation of the selected heavy metals using Atomic Absorption Spectrophotometer (AAS). The range of lead, chromium and arsenic in the fruit items were 1.12 ± 0.077 to 2.899 ± 0.013, 0 to 0.217 ± 0.005 and 0 to 0.078 ± 0.002 mg kg-1 respectively. It was revealed from the results that the level of toxic metals (As, Cr) in almost all fruit samples were within tolerable limit whereas the level of Pd in all of the fruit samples exceeded the acceptable limits of WHO standard value. It was also observed from the results obtained that the concentration of the metals found in the samples from Dhaka regions were considerably higher than that of Chattogram. These metal contributors mainly arising from anthropogenic sources including industrial wastes, automobile emissions, use of fertilizers, pesticides and herbicides in agriculture, paints, sewage and waste disposal. The extended level of these metals causing environmental pollution is hazardous since plants accumulate them. Subsequently, crops uptaking these heavy metals consumed by humans and animals which is detrimental to health. It is therefore very important that necessary actions need to be taken to monitor the level of these deleterious elements in food plants. In decision making, planning and risk assessing this present study will play significant role. Dhaka Univ. J. Sci. 70(1): 22-27, 2022 (January)